Cellular response to chronic psychosocial stress: Ten-year longitudinal changes in telomere length in the Multi-Ethnic Study of Atherosclerosis. (September 2019) - Meier, Helen C.S.; Hussein, Mustafa; Needham, Belinda; Barber, Sharrelle; Lin, Jue; Seeman, Teresa; Diez Roux, Ana
Highlights: Examined if chronic psychosocial stress was longitudinally associated with telomere length changes over time in a diverse, middle-aged cohort . Within-person change from low to high stress over time was associated with sizable telomere attrition. The greatest telomere shortening was observed among those who experienced worsening stress. Individuals with persistently high stress over 10 years experienced less telomere attrition than individuals with persistently low stress. Abstract: Previous studies have demonstrated an inverse association between chronic psychosocial stress and leukocyte telomere length (LTL), a potential marker of cellular aging. However, due to paucity of longitudinal data, responses of LTL and the LTL aging trajectory to changes in chronic stress exposure remain less well understood. Using data from the Stress I and II ancillary studies of the Multi-Ethnic Study of Atherosclerosis, we estimated the 10-year longitudinal (n = 1, 158) associations of within-person changes in chronic stress with changes in LTL, as well as the pooled, cross-sectional associations of chronic stress and LTL (total n = 2, 231). We measured chronic stress from both individual and neighborhood-environment sources. At the individual level, we calculated a summary score of each participant's rating of their ongoing (>6 months) material/social problems as moderately/very stressful on the Chronic Burden Scale. Neighborhood-level stress was measured using a summary score of reverse-coded MESA Neighborhood safety, aesthetic quality, and social cohesion scales. Quantiles of these scores were empirically categorized as high, moderate, or low stress. We then summed these individual- and neighborhood-level categorical variables for a total stress measure. Longitudinal within-person associations were estimated with fixed-effects models, which control for all time-invariant confounding, with additional control for time-varying demographics, lagged behaviors and chronic conditions, and specimen storage duration, as well as correction for regression to the mean. Change from low to high total chronic stress was associated with telomere shortening by 0.054 units [95% confidence interval: −0.095, −0.013] over 10 years. This was consistent with, though stronger in magnitude than, cross-sectional estimates. Change in individual-level stress was the primary driver of this effect. We also found suggestive evidence that 1) individuals with persistently high stress experienced the least shortening of telomeres, and 2) changes in individual-level stress were associated with stronger telomere shortening among women, whereas changes in neighborhood stress were associated with stronger shortening among men. Our findings provide longitudinal support to existing evidence, and point to interesting dynamics in telomere attrition across stress levels and genders.